Ten thank-you letters - Kirk, Daniel (New York, NY : Nancy Paulsen Books, an imprint of Penguin Group (USA), 2014)
While Pig is trying to finish a thank-you note to his grandmother, his best friend Rabbit repeatedly interrupts to borrow supplies for a series of his own notes, thanking all of the special people in their lives.
Keywords: Thank-you notes -- Fiction; Gratitude -- Fiction; Best friends -- Fiction; Friendship -- Fiction